Differentiation of periapical granulomas and cysts by using dental MRI: a pilot study - Jürchott, Alexander; Pfefferle, Thorsten; Flechtenmacher, Christa; Mente, Johannes; Bendszus, Martin; Heiland, Sabine; Hilgenfeld, Tim (International journal of oral science, 2018)
Magnetic resonance imaging (MRI) can differentiate between periapical (apex of a tooth root) cysts and granulomas (inflammations usually caused by infections). MRI is a radiation-free, non-invasive imaging technique, and a team headed by Tim Hilgenfeld at Heidelberg University Hospital in Germany conducted a pilot study to determine whether dental MRI could be used to distinguish periapical cysts from granulomas in 11 patients with confirmed periapical lesions. The authors found that dental MRI allowed for the identification of six characteristics, each of which had the capacity to clearly differentiate between periapical cysts and granulomas. The team’s findings need to be confirmed in future studies with larger numbers of patients. But the results could have a substantial clinical impact in improving diagnoses and avoiding unnecessary surgery in patients with periapical lesions.
Gesehen am 07.11.2019